2015
DOI: 10.4314/gmj.v49i2.2
|View full text |Cite
|
Sign up to set email alerts
|

Foodborne illness among school children in Ga east, Accra

Abstract: SUMMARYBackground: A food borne illness was reported in GaEast district of Greater Accra Region among school children in May, 2007 after eating food provided at school. The objective of the investigation was to determine the source, mode of contamination and the causative agent. Methods: A case-control study was conducted, cases were schoolchildren with abdominal symptoms and controls were children of the same sex and class without any symptom during the same period. The school children were selected by system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 1 publication
1
11
0
Order By: Relevance
“…Food after preparation were kept in cooking pots until service and kept on cooking tripod (locally made cookers) or gas stoves with fire quenched to avoid burning and utility cost. This supports Malm et al (2015) who reported of poor storage facilities and absence of protocols to prevent food poisoning incidences in affected 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64Ghanaian schools in Accra the capital city. This was contrary to the UK condition where all schools had temperature monitoring devices and equipment.…”
Section: School Demographics In Lincolnshire and Ashanti Region Of Ghanasupporting
confidence: 64%
See 1 more Smart Citation
“…Food after preparation were kept in cooking pots until service and kept on cooking tripod (locally made cookers) or gas stoves with fire quenched to avoid burning and utility cost. This supports Malm et al (2015) who reported of poor storage facilities and absence of protocols to prevent food poisoning incidences in affected 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64Ghanaian schools in Accra the capital city. This was contrary to the UK condition where all schools had temperature monitoring devices and equipment.…”
Section: School Demographics In Lincolnshire and Ashanti Region Of Ghanasupporting
confidence: 64%
“…Johnson et al, (2008) recommended for the improvement of food safety in the country. Food poisoning occur in schools in both the developed and developing countries (Ababio & Lovatt, 2015;Malm et al, 2015;Marzano and Balzaratti, 2013;Rodriquez Caturla, 2012;Gupta & Gupta, 2009;Meldrum, Mannion, & Garside, 2009;Santana, Almeida, Ferreira, & Almeida, 2009;Sneed &Henroid, 2007 andDaniels et al, 2002) and the Ministry of Health in Ghana reported of 1348 children suffering from food poisoning in the year 2007 in the capital city alone (Ministry of Health, 2007) however the affected schools in Ghana were reported to have poor food storage facilities and lacked protocols to prevent reoccurrence (Malm et al, 2015;Gupta & Gupta, 2009). In developed countries causes of foodborne illness are often traced and corrective measures taken by management (Meldrum et al, 2009;Daniels et al, 2002) to prevent reoccurrence as part of standard operating procedures.…”
Section: Introductionmentioning
confidence: 99%
“…Rice and groundnut soup, stew, "wakye" and "shitor", "banku", "kenkey", macroni, salad, and water are the commonly contaminated foods in Ghanaian schools. 6,23,26,27 Food handlers in educational institutions are always noted in reported cases of foodborne diseases. 23,26 Indeed, food handlers in Ghanaian schools operate in poor sanitary conditions.…”
Section: Introductionmentioning
confidence: 99%
“…6,23,26,27 Food handlers in educational institutions are always noted in reported cases of foodborne diseases. 23,26 Indeed, food handlers in Ghanaian schools operate in poor sanitary conditions. 28 Furthermore, the hands of food handlers are known as the principal source of food contamination.…”
Section: Introductionmentioning
confidence: 99%
“…In public schools, the Government of Ghana through the School Feeding Program, provide meals to about 1.69 million children nationwide, representing a coverage of 37.4% (MOGCSP, 2016). The risk of food contamination among school children is well documented in literature (Osei-Tutu & Anto, 2016;Malm et al, 2015;Monney et al, 2013;Newman, 2005) and 88% of cases of diarrhea-related diseases worldwide are attributable to unsafe water, inadequate sanitation or insufficient hygiene. Typically, children under five years in crèches go to school with their own packaged drinking water in reusable bottles, refilled polyethylene terephthalate (PET) bottles, commercially packaged bottled water or sachet water from water vendors or from school canteens etc.…”
Section: Introductionmentioning
confidence: 99%